THE INFLUENCE OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Thamrin Thamrin; Luthfi Andriansyah (Jurnal Scientia, 2023)
This research aims to evaluate the impact of work motivation and work discipline on employee performance in the drawing-cutting section of PT Alam Lestari Unggul – Factory Cikupa Tangerang, both individually and simultaneously. This research uses quantitative methods and applies saturated sampling techniques involving 70 respondents. Data analysis involves validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research results show that work motivation has a significant influence on employee performance, and work discipline also has a significant influence on employee performance. Simultaneously, both work motivation and work discipline have a significant effect on employee performance. Data analysis shows that the independent variable and the dependent variable have a very strong relationship with a correlation coefficient value of 0.924. In addition, around 85.4% of the variation in employee performance can be explained by work motivation and discipline, while the remainder, around 14.6%, is influenced by other factors. Hypothesis testing produces a significant F value. Thus, there is a significant influence between work motivation and work discipline on employee performance in the Drawing Cutting section of PT Alam Lestari Unggul – Factory Cikupa Tangerang.